HUBUNGAN PROFIL PELAKU PERJALANAN DENGAN PERILAKU PERJALANAN TERHADAP PUSAT PERBELANJAAN MODERN DI KAWASAN PERKOTAAN YOGYAKARTA - Ratno Tanjung Nasrulloh; Novi Maulida Ni'mah (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2020)
Yogyakarta Urban Area (KPY) which is currently developing rapidly to support the development of urban functions and services in Yogyakarta, one of which is the trade and services sector. This can be seen from the number of modern centers in KPY. The interaction between land and transportation has been accepted by researchers from various disciplines for decades. Therefore, examining the behavior of the behavior towards the center becomes one of the bases in planning urban morphology and rather the morphology influences the travel behavior of the community. This study seeks to examine the journey of people to urban centers in the Yogyakarta urban area with case studies of Mall Ambarukmo Plaza, Lippo Mall, and Jogja City Mall. The research method used is cross classification with variables consisting of the profile of the traveler and behavior. Based on the analysis, it can be neglected that the profile of the traveler to the modern mall center (gender, age, education level, occupation, income and place of residence (domicile) has no relationship to his travel behavior (frequency, intention, time) in KPY. Mostly or an average of more than 60% of the trip attractions still come from within KPY.